I shouldn't talk of medicine only: Biomedical and religious frameworks for understanding antiretroviral therapies, their invention and their effects. Issue 10 (3rd October 2018) - Kelly-Hanku, Angela; Aggleton, Peter; Shih, Patti
ABSTRACT: Medical pluralism offers a long-standing means of analysing the different ways in which health and illness can be interpreted and responded to. It is not unusual for multiple health systems and meanings to co-exist at any one moment in time, offering different ways of understanding and responding to illness and disease. In addition to biomedical frameworks, religious beliefs offer another important means of facilitating healing. Based on qualitative interviews with 36 people living with HIV on antiretroviral therapies (ART) in Papua New Guinea (PNG), this paper examines the ways in which people bring together and synthesise religious and biomedical therapeutic approaches to the treatment and management of HIV. For most, ART is viewed as a divine gift to complement a regime of spiritual salvation, and adherence to treatment carries with it strong religious undertones. At the same time, ART provides a sense of hope for those living with a virus that was previously associated only with death. Brought together, these narratives provide important insights into the meanings of ART and the role of religion, prayer and repentance for people in PNG. The study also provides new insight into how people with HIV actively synthesise different approaches to health and healing.